Analisis Potensi Sektor Basis Dan Non Basis Ekonomi PadaPerubahan Struktur Perekonomian Di Kota SalatigaTahun 2010-2015 - Ningrum, Puspasari Ayu; , Dr. Daryono Soebagyo M.Ec (2017)
This study entitled "Analysis of Potential Base and Non-Base Economy Sector on Structure Changes of Economic in Salatiga City Year of 2010-2015". The main purpose of the research is to analyze the sector that has potentially be a base ectorand determine Structure Changes of Economic in Salatiga. The method used is Location Quotient (LQ) and Shift Share Esteban Marquillas. and this study uses data of GDP. The results of analysis LQ and Shift Share Esteban Marquillas show that between 2010-2015 that became the base sector in Salatiga is the gas sector and the electricity supply, water supply, waste management, waste and recycling, processing industry, construction, provision of ccommodation and meals drinking, financial services and insurance, real estate, corporate services, government administration, defense and compulsory social security, education services, health services and social activities as well as changes in the economic structure of the modern sector to traditional sector namely agriculture, forestry and fisheries into a sector basis in the year 2013-2015.